2001
DOI: 10.1098/rspb.2001.1715
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation across a climatic gradient despite small effective population size in the rare sapphire rockcress

Abstract: When assigning conservation priorities in endangered species, two common management strategies seek to protect remnant populations that (i) are the most genetically divergent or (ii) possess the highest diversity at neutral genetic markers. These two approaches assume that variation in molecular markers reflects variation in ecologically important traits and ignore the possibility of local adaptation among populations that show little divergence or variation at marker loci. Using common garden experiments, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 54 publications
13
135
2
1
Order By: Relevance
“…We believe that information from DNA markers together with phenotypic performance and population history may provide reliable guidelines in choosing populations for practical and for conservation purposes. However, setting conservation priorities based exclusively on the diversity of molecular markers might lead to the loss of locally adapted populations [32].…”
Section: The Chicken Ancestor and The Need For Conservationmentioning
confidence: 99%
“…We believe that information from DNA markers together with phenotypic performance and population history may provide reliable guidelines in choosing populations for practical and for conservation purposes. However, setting conservation priorities based exclusively on the diversity of molecular markers might lead to the loss of locally adapted populations [32].…”
Section: The Chicken Ancestor and The Need For Conservationmentioning
confidence: 99%
“…In a recent study where desert and Mediterranean plants of Hordeum spontaneum were found to be adapted to their locations and differentiated in phenotypic traits (Volis et al, 2002b), no concordance between quantitative and molecular (allozyme) pairwise genetic distances was detected (Volis et al, 2002a). Several studies in which patterns of quantitative trait variation were strongly associated with climate or distinct habitats also demonstrated a lack of correspondence between molecular and quantitative trait variation patterns (Karhu et al, 1996;Knapp and Rice, 1998;McKay et al, 2001;Steinger et al, 2002). In other studies where genetic subdivisions at quantitative and molecular markers were compared in their relation to geographic subdivision but without tests of local adaptation/ association with environmental parameters, or were compared without any reference to spatial location/ environmental differences, the outcomes varied from a close match (Lagercrantz and Ryman, 1990;Kuittinen et al, 1997;Morgan et al, 2001) to complete disagreement (Podolsky and Holtsford, 1995;Black-Samuelsson et al, 1997;Heaton et al, 1999;Storz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Local adaptation might be suspected because of the existence of an environmental gradient such as latitude (Toräng et al, 2015) or altitude (Alberto et al, 2011), or because of the existence of several contrasting environments, such as sea and fresh water (DeFaveri and Merilä, 2014). In addition, common garden experiments are also used to study the consequences of local adaptation for conservation (McKay et al, 2001) or even for ecosystem functioning (Bassar et al, 2010). Despite its name, and although it has been used extensively with plants (Linhart and Grant, 1996), this experimental approach can also be applied to a large variety of organisms including fish (Bassar et al, 2010;DeFaveri and Merilä, 2014), invertebrates (Spitze, 1993;Luttikhuizen et al, 2003) and small mammals (Bozinovic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%